G19 An evaluation of fracture clinic referrals in Ireland's busiest Paediatric Emergency Department. (7th April 2014) - Ramasubbu, B; Caffrey, R; Mc Namara, R; Deiratany, S; Okafor, I
Abstract : Background: Injuries account for about 18% of all paediatric emergency department presentations. Of these, a significant amount will have fractures that will require orthopaedic follow-up. These clinics tend to be very busy and result in poor patient and staff satisfaction. During August an average of 60 patients were seen in Orthopaedic fracture clinic per day with a range of 45–72 patients. Aims: To assess the accuracy and necessity of fracture clinic referrals from our Emergency Department and to suggest an approach and this might safely reduce the referral numbers. Methods: All fracture clinic referrals from Temple Street Emergency Department in August 2013 were retrospectively audited. Each patient's electronic patient notes and official radiology report were reviewed. Data was recorded on Excel. Results: There were 339 fracture clinic referrals in August 2013. 213 (63%) had fractures as reported by Consultant Radiologist. 126 (37%) had no fracture confirmed and of these 24 (19%) had no fracture seen in the emergency department but were referred as clinically fractured. 33(10%) were buckle fractures. There were 21 (6.2%) finger injuries referred. Of ankle injuries referred (n = 43) 14 (33%) were confirmed Salter-Harris 1 or 2 or avulsion fractures of the lateral malleolus and 16 (37%) were suspected of same. Discussion: Buckle fractures (n = 33) accounted for 10% of fracture clinic referrals and current evidence suggests that this type of fracture is better managed in a removable splint and costly follow-up orthopaedics clinic appointments may not be required. There were 21 (6.2%) finger injuries referred and these fractures can be managed in a buddy strap and do not require specialist orthopaedic follow-up in an outpatient setting. Additionally, 30 (70%) of the ankle injuries referred were clinically insignificant 'low risk fractures' and can be managed by supportive splinting in a removable ankle brace and return to activities as tolerated by the patient. Conclusions: Through education and policy change such as the establishment of an ANP led clinic or a virtual clinic within our emergency department; we could safely and efficiently reduce orthopaedic fracture clinic referrals by over 30%.